Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 1082 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Asparagopsis taxiformis (Delile) Trevis.", "HasCoordinate is TRUE" ] } The dataset includes 1082 records from 38 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000774-160118175350007/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences